Canine reproductive ultrasound examination for predicting future sperm quality - England, Gary C.W.; Bright, L.; Pritchard, B.; Bowen, I. Mark; De Souza, M.; Silva, L.D.M.; Moxon, Rachel (Wiley, 2016)
The reproductive potential of male animals is commonly evaluated using a breeding soundness examination incorporating B-mode ultrasound examination of the testes and recently Doppler ultrasound examination of the testicular arteries. These techniques may detect testicular normality or pathology, and while some measured parameters are associated with semen quality at the time of ultrasound examination, few studies have investigated the relationship with future semen quality. We hypothesized that B-mode and Doppler ultrasound measurements would correlate with future semen quality. Within two studies, we investigated the relationship between ultrasound measured testicular volume, testicular echogenicity, testicular homogeneity, subjective assessment of the testicular parenchyma, testicular artery resistance index, and pulsatility index with subsequent semen quality. Fifty-five normal fertile dogs of which 29 had stable semen quality and 26 had a subsequent decline in semen quality were examined during a 6-month period commencing 62 days after the ultrasound examination. Statistical analysis showed that no ultrasound parameters were predictive of future total sperm output or percentage live normal sperm. However, mean testicular echogenicity was positively related to future sperm motility (t = 2.202, p = .039). We conclude that quantitative ultrasound assessment of the appearance of the testicular parenchyma has potential for the evaluation of future semen quality in dogs.